2016
DOI: 10.1016/j.physletb.2016.05.010
|View full text |Cite
|
Sign up to set email alerts
|

The Higgs mass and natural supersymmetric spectrum from the landscape

Abstract: In supersymmetric models where the superpotential mu term is generated with mu<< m_{soft} (e.g. from radiative Peccei-Quinn symmetry breaking or compactified string models with sequestration and stabilized moduli), and where the string landscape 1. favors soft supersymmetry (SUSY) breaking terms as large as possible and 2. where the anthropic condition that electroweak symmetry is properly broken with a weak scale m_{W,Z,h}~100 GeV ({\it i.e.} not too weak of weak interactions), then these combined landscape/a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 64 publications
(70 reference statements)
2
45
0
Order By: Relevance
“…Several factors intervene to counteract this expectation [11]. First, electroweak symmetry must be properly broken: no charge or color breaking vacua (CCB) are allowed.…”
Section: Introductionmentioning
confidence: 99%
“…Several factors intervene to counteract this expectation [11]. First, electroweak symmetry must be properly broken: no charge or color breaking vacua (CCB) are allowed.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, if the soft terms scan as in the string landscape picture, then their moduli-mediated contributions may be expected to be parametrized by a continuous value. For models which generate a small µ term ∼ 100 GeV from multi-TeV soft terms, such as radiative Peccei-Quinn breaking [28], it has been suggested that the statistical pull by the landscape towards large soft terms, coupled with the anthropic requirement of m weak ∼ 100 GeV, acts as an attractor towards natural SUSY soft term boundary conditions [29].…”
mentioning
confidence: 99%
“…In refs. [93] and [77], it is noted that large c m solutions may be favoured by a string theory landscape which prefers large soft terms, consistent with the anthropic weak scale requirement m W,Z,h ∼ 100 GeV. In figure 5, we show variation of ∆ EW , m h and mt 1 versus a 3 (left-column) and tan β (right-column).…”
mentioning
confidence: 61%
“…For instance, if the soft terms scan as in the string landscape picture [74], then their moduli-mediated contributions may be expected to be parametrized by a continuous value. For models which generate a small µ term ∼ 100 GeV from multi-TeV soft terms, such as in the KimNilles mechanism [75] with radiative Peccei-Quinn breaking [76], it has been suggested that the statistical pull by the landscape towards large soft terms, coupled with the anthropic requirement of m weak ∼ 100 GeV, acts as an attractor towards natural SUSY soft term boundary conditions [77].…”
Section: Natural Generalized Mirage Mediationmentioning
confidence: 99%